Nicotinic Acetylcholine Receptor Mediates Nicotine-Induced Actin Cytoskeletal Remodeling and Extracellular Matrix Degradation by Vascular Smooth Muscle Cells - Gu, Zhizhan (2012)
Cigarette smoking is a significant risk factor for atherosclerosis, which involves the invasion of vascular smooth muscle cells (VSMCs) from the media to intima. A hallmark of many invasive cells is actin cytoskeletal remodeling in the form of podosomes, accompanied by extracellular matrix (ECM) degradation. A7r5 VSMCs form podosomes in response to PKC activation. In this study, we found that cigarette smoke extract, nicotine, and the cholinergic agonist, carbachol, were similarly effective in inducing the formation of podosome rosettes in A7r5 VSMCs. α-Bungarotoxin and atropine experiments confirmed the involvement of nicotinic acetylcholine receptors (nAChRs). Western blotting and immunofluorescence experiments revealed the aggregation of nAChRs at podosome rosettes. Cycloheximide experiments and media exchange experiments suggested that autocrine factor(s) and intracellular phenotypic modulation are putative mechanisms. In situ zymography experiments indicated that, in response to PKC activation, nicotine-treated cells degraded ECM near podosome rosettes, and possibly endocytose ECM fragments to intracellular compartments. Invasion assay of human aortic smooth muscle cells indicated that nicotine and PKC activation individually and synergistically enhanced cell invasion through ECM. Results from this study suggest that nicotine enhances the ability of VSMCs to degrade and invade ECM. nAChR activation, actin cytoskeletal remodeling and phenotypic modulation are possible mechanisms.